1999
DOI: 10.1046/j.1365-2419.1999.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate fluctuations and the spring invasion of the North Sea by Calanus finmarchicus

Abstract: This version is available at https://strathprints.strath.ac.uk/18569/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 47 publications
6
90
1
Order By: Relevance
“…It shows that the surface has warmed throughout the region. Heath et al (1999) proposed that the decline of C. finmarchicus abundance was a result of a reduction in overwintering habitat available due to a decrease in the volume of Norwegian Sea Deepwater. Warm-water zooplankton species have become prevalent in this region (Beaugrand et al 2002, Beaugrand 2003.…”
Section: Discussionmentioning
confidence: 99%
“…It shows that the surface has warmed throughout the region. Heath et al (1999) proposed that the decline of C. finmarchicus abundance was a result of a reduction in overwintering habitat available due to a decrease in the volume of Norwegian Sea Deepwater. Warm-water zooplankton species have become prevalent in this region (Beaugrand et al 2002, Beaugrand 2003.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that the warm temperate species C. helgolandicus was posi-tively related to the NAO although the relationship was weaker and with a 1 yr lag. Many hypotheses were proposed to explain the link between the NAO and these species: wind-induced turbulence and prey-predator interactions, the influence of temperature on competition between both species, bottom-up control, changes in biogeographical boundaries between both species, the volume of Norwegian Sea Deep Water in which C. finmarchicus is known to overwinter and the flow of the European shelf edge current (Heath et al 1999, Beaugrand 2009). …”
Section: Introductionmentioning
confidence: 99%
“…One explanation for the temporal Patterns Seen in the 2 Calanus species is that Atlantic influence and inflow (Corten 1990, Stephens et al 1998) into the North Sea were greater in the 1960s and more Calanus were imported: C. finmarchicus from overwintenng 1.ocations beyond the contmental shelf and C. helgolandicus from the north and West of Scotland via the Fair lsle Current (Backhaus et al 1994, Heath et al 1999. The waning of relatively warm Atlantic inflow left a signature of falling temperatures (See Fig.…”
mentioning
confidence: 99%